Power energy management strategy of micro-grid system - Mohd Fauzi, Mohamad Yusof; Abu Zaharin, Ahmad (IEEE, 2017)
In this paper, the power energy management of the micro-grid system that consists of photovoltaic (PV), wind and energy storage systems is analyzed. The micro-grid is proposed to cater the load demand in standalone mode. The operation is set the PV to act as a primary source follow by the wind energy and the energy storage as a back-up source. The main focus in this paper is to propose the strategy of energy management of renewable energy sources. The design consideration and analysis are setup in Matlab/Simulink environment.